Recent epifaunal benthic foraminifera counts in surface sediment samples from the Southeast Pacific - Sebastián Garrido; Magali Schweizwer; Dharma Reyes-Macaya; María Yolanda Núñez; Alexis Castillo Bruna; Babette A A Hoogakker (PANGAEA, 2025)
This study developed a unified taxonomic classification system for recent epifaunal benthic foraminifera species collected from surface sediment samples along the Southeast Pacific margin, including Cibicidoides wuellerstorfi, C. lobatulus, C. cf. ungerianus, Planulina ariminensis, P. ornata, and P. limbata. Morphological characteristics of these epifaunal benthic foraminifera specimens, such as test shape, periphery, chamber inflation, elongation, suture curvature, and wall porosity, were measured between December 2022 and June 2023. Furthermore, variations in morphological features like planoconvex tests, proloculus size, suture curvature, and pore patterns were observed among these foraminifera. The surface sediment samples were collected off the coasts of Chile and Peru between 1962 and 2014, covering latitudes from 12.70°S to 44.09°S and water depths ranging from 24 to 3,267 m. The temporal coverage of the samples spans the Holocene, with a focus on the late Holocene and modern samples. These samples were collected using various gear devices, including a multicorer (Sonne 156, Sonne 211, Meteor 92), a box corer (BIAC072014), a Petersen grab (USNS Eltanin), and a gravity core (Sonne 161). Detailed morphological examinations of the specimens were conducted using TM4000Plus HITACHI SEM imaging and a Leica S8 APO stereomicroscope, complemented by manual illustrations. The unified taxonomic criteria will enhance the accuracy of foraminifera-based proxies, such as stable isotopes and morphological studies, which are vital for paleoceanographic reconstructions.
In: Garrido, S et al. (2025): Recent epifaunal benthic foraminifera species of surface sediment samples along the Southeast Pacific margin [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965601